Desain Dan Analisa Bidirectional Inverter Untuk Menggerakkan Motor Induksi Tiga Fasa Dengan Sumber Baterai 48 V - Bangun Suryadi; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The supply of fossil energy is already at a critical time. Renewable energy such as sunlight and others are expected to cope with the energy crisis. The existing renewable still in the form of direct voltage. In automobile applications stored in the battery, which is used as the energy of the induction motor. So that a bidirectional inverter is needed to convert that directional voltage to rotate the induction motor. This research purposes to design and analyze bidirectional inverter to supply three phase Induction motor 380 V with 48 V Battery as the source. In Inverter mode, motor is supplied by battery, after the voltage is increased by the transformer. While it charge the battery through motor rotation in rectifier mode, after the voltage is decreased by the transformer. The design simulation is done by matlab simulink. It shows the performance able to achieve tehe minimum requirement of design specificationKeywords :Renewable energy, Bidirectional Inverter, SPWM, Three Phase InductionMotor, automobile application, MATLAB.